PID Control for Cart and Pole system: Simulation and Experiment - Dang, Thai-Bao; Ngo, Truong-Doan-Hy; Tran, Thanh-Danh; Vo, Thi-Kieu-Tien; Lai, Nguyen-Ngoc-Truc; Huynh, Thi-My-Linh; Nguyen, Thi-My-Hang; Nguyen, Thi-My; Le, Tuong-Vy; Pham, Khanh-Hung; Huynh, Nguyen-Cuong; Nguyen, Anh-Tuan; Nguyen, Thanh-Trung (Peneliti Teknologi Teknik Indonesia, 2024)
Inverted pendulum (IP) is a single input-multi output (SIMO) nonlinear system that is popular in laboratories of control engineering. In this paper, we propose a structure of the PID control method – the most popular control method in the industry - for the cart and pole (C&P) system- a kind of IP. In this case, a suitable structure can help single input-single output (SISO) linear controllers to balance well. By this combination, the PID method can be used to stabilize this model at the equilibrium point. This controller is proven to work well in simulation. Therefore, we also present an experimental model which is created from the STM32F4 Discovery board for testing this algorithm. The experiment results again confirm the suitability of the method in simulation. Therefore, a survey of PID calibration is examined. The experimental survey confirms the suitability of this PID controller with theoretical points. The results from this study can be used to examine and train algorithms for learners in control laboratories.